Incidence and severity of pertussis hospitalisations in infants aged less than 1 year in 37 hospitals of six EU/EEA countries, results of PERTINENT sentinel pilot surveillance system, December 2015 to December 2018 - Merdrignac, Lore; Aït El Belghiti, Fatima; Pandolfi, Elisabetta; Jané, Mireia; Murphy, Jane; Fabiánová, Kateřina; García Cenoz, Manuel; Flem, Elmira; Guillot, Sophie; Tozzi, Alberto E; Carmona, Gloria; Habington, Adele; et al. (Euro surveillance, 2021)
IntroductionPERTINENT is a pilot active surveillance system of infants hospitalised with pertussis in six European Union/European Economic Area countries (37 hospitals, seven sites).AimThis observational study aimed to estimate annual pertussis incidence per site from 2016 to 2018 and respective trends between 2017 and 2018. Pertussis cases were described, including their severity.MethodsWe developed a generic protocol and laboratory guidelines to harmonise practices across sites. Cases were hospitalised infants testing positive for Bordetella pertussis by PCR or culture. Sites collected demographic, clinical, laboratory data, vaccination status, and risk/protective factors. We estimated sites' annual incidences by dividing case numbers by the catchment populations.ResultsFrom December 2015 to December 2018, we identified 469 cases (247 males; 53%). The median age, birthweight and gestational age were 2.5 months (range: 0-11.6; interquartile range (IQR): 2.5), 3,280 g (range: 700-4,925; IQR: 720) and 39 weeks (range: 25-42; IQR: 2), respectively. Thirty cases (6%) had atypical presentation either with cough or cyanosis only or with absence of pertussis-like symptoms. Of 330 cases with information, 83 (25%) were admitted to intensive care units including five deceased infants too young to be vaccinated. Incidence rate ratios between 2018 and 2017 were 1.43 in Czech Republic (p = 0.468), 0.25 in Catalonia (p = 0.002), 0.71 in France (p = 0.034), 0.14 in Ireland (p = 0.002), 0.63 in Italy (p = 0.053), 0.21 in Navarra (p = 0.148) and zero in Norway.ConclusionsIncidence appeared to decrease between 2017 and 2018 in all but one site. Enhanced surveillance of hospitalised pertussis in Europe is essential to monitor pertussis epidemiology and disease burden.
Keywords: Evropská unie; Ireland; Europe; France; Bordetella pertussis; Incidence; pertusová vakcína; mužské pohlaví; Hospitals; Evropa; hospitalizace; vakcinace; Humans; senioři; Itálie; pertuse; Hospitalization; pertussis incidence; hospital surveillance; kojenec; Infant; Whooping Cough; lidé; incidence; novorozenec; Norway; Czech Republic; Francie; Česká republika; Vaccination; Aged; Irsko; Italy; Male; European Union; Pertussis Vaccine; Norsko; active surveillance; Infant, Newborn; pertussis; nemocnice